Pengaruh Word Of Mouth, Persepsi Harga dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen pada Noira Coffee Kendari - Ramadhan, Ridho; Madjid, Rahmat; Razak, Abdul (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the influence of Word of Mouth (WOM), price perception, and product quality on consumer purchasing decisions at Noira Coffee Kendari, both simultaneously and partially. The study employs a quantitative approach using a survey method involving 105 respondents, with data collected via a structured questionnaire. The data were analysed using multiple linear regression as an inferential statistical technique to test the relationships between variables. The results indicate that, simultaneously, WOM, price perception, and product quality have a significant influence on purchasing decisions. Partially, WOM has no significant influence, whilst price perception has a negative and significant influence, and product quality has a positive and significant influence on purchasing decisions. These findings indicate that consumer purchasing decisions at Noira Coffee are more determined by product quality and the alignment of price with perceived value than by word-of-mouth communication. The main implication of this study emphasises the importance of maintaining product quality and setting prices that are balanced with consumers’ perceived value as a key strategy for enhancing purchasing decisions